THE USE OF ROLE-PLAYING GAMES IN SWIMMING LESSONS WITH PRESCHOOL CHILDREN (Physical Culture and Sport: Scientific Perspective, 2024)
The article proves the effectiveness of the method of using role-playing games in swimming lessons with preschool children. The method was used in the process of initial swimming training for children 5-6 years old who had no previous experience of attending organized classes. Classes were held in the Dolphin swimming pool in Chernivtsi. 2 times a week for 45 minutes. A total of 28 classes were held.The plot of the fairy tales was adapted to the content of swimming lessons and the solution of the main tasks of the initial stage of training: the study of contrasting exercises for mastering with water; learning how to breathe correctly; mastering the skill of immersion under water, floating, keeping on the surface of the water in a horizontal position; gliding study; Learn the alternating work of the legs on the chest and on the back in an unsupported position.According to the results of control tests of swimming fitness, statistically significant differences were found in 10 indicators (out of 13) in favor of children who studied according to the experimental method of using role-playing games in comparison with children who studied under the program "Fairytale Swimming". These are: running a 6-meter segment in the water with support on the bottom of the pool; lifting objects from the bottom of the pool in 30 seconds; "Float"; maximum number of exhalations into the water; breath retention while inhaling; holding breath while exhaling; "Star" on the chest; "Star" on the back; alternating work of the legs with a crawl on the chest near a fixed support without holding breath; alternating work of the legs with a crawl with a movable support without holding your breath.Research methods: theoretical analysis and generalization of scientific and methodological literature; analysis of methods of teaching swimming to preschool children; pedagogical testing; pedagogical experiment; Methods of Mathematical Statistics.
Keywords: swimming lessons; 5-6 years old children; role-playing games